2010
DOI: 10.1080/09585192.2010.483852
|View full text |Cite
|
Sign up to set email alerts
|

Counterproductive behaviour at work: an investigation into reduction strategies

Abstract: The present study examined the interrelation of personality characteristics, organizational justice, organizational citizenship behaviour (OCB), and counterproductive work behaviour (CWB). An anonymous questionnaire survey was conducted, with 1,662 participants representing a wide variety of jobs across heterogeneous organizations in Thailand. Statistical analysis indicated that CWB can be predicted by the following personality characteristics; conscientiousness, agreeableness, self-esteem, extraversion, neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 40 publications
0
48
0
5
Order By: Relevance
“…As earlier noted, CWBs embrace a multiplicity of behaviors such as absenteeism, dissemination of destructive reports, disruption, stealing, sexual harassment, or uncooperative attitude among others (Chang & Smithikrai, 2010). The diversity of these detrimental acts can be categorized into fi ve main classes, namely: abuse, production deviation, sabotage, theft, and withdrawal (Spector et al, 2006).…”
Section: Dimensions Of Counterproductive Work Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…As earlier noted, CWBs embrace a multiplicity of behaviors such as absenteeism, dissemination of destructive reports, disruption, stealing, sexual harassment, or uncooperative attitude among others (Chang & Smithikrai, 2010). The diversity of these detrimental acts can be categorized into fi ve main classes, namely: abuse, production deviation, sabotage, theft, and withdrawal (Spector et al, 2006).…”
Section: Dimensions Of Counterproductive Work Behaviormentioning
confidence: 99%
“…(Spector & Fox, 2005). CWBs at the organizational level relate to deviant behaviors, such as calling in sick when one is not, withdrawal efforts, long hours of break, cyberloafi ng, misuse/damage of the employer's assets, stealing, sabotage, etc., which affect the organization (Chang & Smithikrai, 2010).…”
mentioning
confidence: 99%
“…OCB is generally defined as behavior that goes beyond the formal requirements of the job and is beneficial to the organization (Chang & Smithikrai, 2010). Examples of OCB may include assisting colleagues with their tasks, devoting time to assist new entrants to the organization, defending their F o r P e e r R e v i e w 6 organizational reputation, or even voluntary salary-cut to support the organizations.…”
Section: Literature Review and Theoretical Framingmentioning
confidence: 99%
“…Christ et al, 2003;Organ, 1988;Strobel et al, 2013). It is suggested that OCB acts as a 'behavioral catalyst', promoting commitment (Bogler and Somech, 2004;Chang and Smithikrai, 2010), reducing absenteeism (Cohen and Keren, 2010) and enhancing skill development (Dalal, 2005), which in turn leads to higher productivity and efficiency (e.g. Carpenter, Berry, and Houston, 2014; Somech and Ron, 2007;Spence, Ferris, Brown, and Heller, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…STEFAN TOKARSKI KRZYSZTOF TOKARSKI JOANNA SIKORA When making a balance of economic data quantifying the results of the surveyed companies were divided into four quartiles 6 -compartments assigned to specifi c revenues. The study included companies representing: state ownership of the Treasury, private ownership and foreign ownership 7 .…”
Section: Methods and Research Organizationmentioning
confidence: 99%